Effect of solid/liquid ratio during curing time fly ash based geopolymer on mechanical property - Rahmiati, T. (Trans Tech Publications Ltd, 2015)
Geopolymer is produced from the alkali activation of materials rich in Si and Al such as fly ash. Based on the experimental and characterization result, solid to liquid ratio influenced the setting time and compressive strength of geopolymer in order to have good mechanical property. The optimum setting time and compressive strength were obtained at 3: 1 solid to liquid ratio. Optimum curing time reach at 14 days. Â© (2015) Trans Tech Publications, Switzerland.